Radiology Technologists' Perspective on Medical Imaging Device Use and Related Technologies: a Cross-sectional Survey with Respect to Hospital Type - AKYURT, NURAN (My University, 2022)
This study aimed to evaluate radiology technicians\" view on the use of medical imaging devices and related technology. A total of 142 radiology technicians from Turkey were included on a voluntary basis in this cross-sectional questionnaire-based study. The questionnaire form elicited items on sociodemographic and occupational characteristics and personal opinions regarding the use of medical imaging devices and related technology. Majority of technicians agreed or strongly agreed that they prefer the latest technology medical imaging devices (32.4 and 54.2%) and there is an increase in the number of medical imaging devices (36.6 and 35.9%) and medical imaging examinations (32.4 and 43.7%), while the growing societal demands in field of health have a role in the increase in the number of medical imaging devices (34.5 and 32.4%). However, a relatively lower percentage of technicians agreed or strongly agreed that the latest technology medical imaging devices should be purchased no matter how much it costs (31.7 and 33.8%) and the yearly increase in the number of imaging examinations indicates provision of an improved healthcare (21.1 and 23.2%). A higher agreement was reported by private hospital (3.9 +/- 1.1, p = 0.035) and university hospital (4.1 +/- 1.1, p = 0.009) employees vs. state hospital employees (3.4 +/- 1.3) on the growing societal demands in field of health to have a role in the increase in the number of medical imaging devices. Apart from this, no significant difference was noted in opinions of technicians on the use of medical imaging devices and related technology with respect to hospital types. Our findings indicate that radiology technicians report a considerable imaging workload volume and a preference for working with higher number of medical imaging devices particularly those with the latest technology, whereas they also emphasize that the yearly increase in the number of imaging examinations does not indicate provision of an improved healthcare, and the cost should always be a criterion when purchasing the latest technology devices.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Klinik Tıp; Klinik Tıp (MED); RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; CLINICAL MEDICINE; Clinical Medicine (MED); Radyoloji ve Ultrason Teknolojisi; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiological and Ultrasound Technology; Radiology, Nuclear Medicine and Imaging; Medical imaging; Devices; Technology; Utilization; Radiology technicians; CARE; Medical imaging; Devices; Technology; Utilization; Radiology technicians